1977
DOI: 10.1063/1.435060
|View full text |Cite
|
Sign up to set email alerts
|

Reaction product identification from O(3P)+benzene, toluene, and 1,3,5-trimethylbenzene collisions in crossed molecular beams

Abstract: Although absolute rate coefficients have been measured for a number of reactions of aromatic molecules with O(3P) atoms, very little is known about the mechanisms of these reactions. In order to identify the products of O atom–aromatic molecule reactions, the products of single reactive collisions between oxygen atoms and benzene, toluene, and 1,3,5,-trimethylbenzene have been observed in crossed molecular beam experiments. The products were detected with a quadrupole mass spectrometer. Two product paths were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
1

Year Published

1980
1980
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 30 publications
2
28
1
Order By: Relevance
“…It is appropriate here to comment on the nature of the coproduct of the spin-forbidden CO-forming channel. Clearly, the early suggestion 37 that the coproduct of CO is the open chain hydrocarbon 3-penten-1-yne was erroneous, as demonstrated by the present and previous theoretical work, 24 , 48 , 51 by the direct observation of cyclopentadiene in the experiment by Taatjes et al 24 through accurate measurements of the ionization efficiency curve of the product, and also by the present and previous 10 , 51 CMB studies.…”
Section: Discussionmentioning
confidence: 73%
“…It is appropriate here to comment on the nature of the coproduct of the spin-forbidden CO-forming channel. Clearly, the early suggestion 37 that the coproduct of CO is the open chain hydrocarbon 3-penten-1-yne was erroneous, as demonstrated by the present and previous theoretical work, 24 , 48 , 51 by the direct observation of cyclopentadiene in the experiment by Taatjes et al 24 through accurate measurements of the ionization efficiency curve of the product, and also by the present and previous 10 , 51 CMB studies.…”
Section: Discussionmentioning
confidence: 73%
“…Figures 10 and 11 also show that the products c-C 5 H 6 + CO, phenol, and benzene oxide/oxepin are major, at least in some conditions, while the products phenoxy radical + H, c-C 6 H 4 + H 2 O, the ketone S3 and BDK S8 are always minor. These results are in agreement with earlier experimental observations for key products such as phenol and CO. [19][20][21] As can be seen, the fractions of the various products depend in a complex way on T and P. In general, an increase of temperature enhances the yields of c-C 5 H 6 + CO, phenoxy radical + H, and c-C 6 H 4 + H 2 O. On the other hand, increasing the pressure will reduce the yields of c-C 5 H 6 + CO, phenoxy radical + H, and c-C 6 H 4 + H 2 O, but increase those of phenol and benzene oxide/oxepin.…”
Section: Iii2 Quantification Of the Product Distribution Resulting mentioning
confidence: 99%
“…Several experimental [36][37][38][39][40] and theoretical 41,42 investigations on reactions of O͑ 3 P͒ with aromatic compounds have been reported. Sibener et al 36 investigated the reaction of O͑ 3 P͒ +C 6 H 6 with crossed-molecular beams and concluded that the initially formed triplet biradical C 6 Barry et al 38 investigated the reaction of a crossedmolecular beam of O͑ 3 P͒ +C 6 H 6 at a collision energy of 16.5 kcal mol −1 and reported little ͑0.8 kcal mol −1 ͒ rotational excitation of the OH product detected by LIF; the results indicate that the reaction might proceed directly via an OϪHϪC collinear transition structure.…”
Section: Dynamics Of Reactions O" 1 D… + C 6 H 6 and C 6 D 6 I Intromentioning
confidence: 99%